High-performance organic-inorganic hybrid piezo-nanogenerator via interface enhancedpolarization effects for self-powered electronic systems - Dhakras, Dipti; Ogale, Satishchandra (Advanced Materials Interfaces, 2016)
An electrospun fi ber based wearable organic-inorganic hybrid piezonanogenerator compose of suitably engineered P(VDF-TrFE) and BaTiO3 nanostructures is reported. In the case of the device with an electrospun mat of piezoelectric beta-phase P(VDF-TrFE) and BaTiO3 nanoparticulates fi lled in the interfi ber open spaces, a power density of 16 mu W cm(-2) is realized at an applied impact of 0.02 MPa (which essentially corresponds to the thumb pressure). A similar device, with BaTiO 3 additionally embedded in the P(VDF-TrFE) fi bers during their formation, renders a signifi cantly higher peak power density of 28 mu W cm(-2) with instantaneous power density of approximate to 8.8 mu W cm(-2) at the same touch pressure. This performance is attributed to the high density of interfaces in such a device and the corresponding enhancement in the dielectric response. It is demonstrated that the power generated from such a hybrid device structure can be used for small scale applications such as charging a mobile phone.